Experimental Study on Bow Slamming of a Ship - Andi Dian Eka Anggriani; Baso, Suandar; Bochary, Lukman; Rosmani; Asis, Muhammad Akbar; Mubarak, Muh Miftach Aqsa; La Ode Gaffar (International Journal of Metacentre, 2023)
This study discusses about the critical issue of slamming phenomena in ship design, emphasizing its impact on ship safety, environmental concerns, and fuel consumption. The drop tests has been used to investigate bow slamming pressures and internal strain at various drop angle. The results indicated peak pressures at different sensors, with higher drop angles resulting in increased impact pressures and internal strains due to augmented velocity, angular momentum, surface area contact, hydrodynamic effects, and gravitational forces.